The Phenomenon of Artificial Intelligence (AI) Dependence in an Islamic Perspective on Adolescents - Didik Himmawan; Mohamad Wildan Soferino; Rindi Ariyani; Kahfiyah Rasiyani Eka Jayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The use of AI technology requires regulation and ethics, as well as the responsible development of AI technology. Regulation and ethics can help ensure that AI technology is used for good purposes and does not harm society. Meanwhile, the development of responsible AI technology can help society to trust and accept AI technology. The research method used in this study is a qualitative method with a literature study approach. The research topic chosen is